Pocketbook voting and social preferences in referenda - Johannes Meya; Panu Poutvaara; Robert Schwager (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We study the role of self-interest and social preferences in referenda. Our analysis is based on collective purchasing decisions of university students on deep-discount flat-rate tickets for public transportation and culture. Individual usage data allows quantifying monetary benefits associated with each ticket. We find that turnout is much higher among students who benefit a lot from having a ticket, suggesting instrumental voting. In each referendum, a majority votes in line with self-interest, providing strong evidence for pocketbook voting. However, social preferences like altruism, public good considerations and paternalism shift the vote of a sizeable minority against their own financial interest.
Keywords: D72; H41; D64; 330